Electroanalytical study of fluvoxamine - Nouws, Henri P. A. (2013)
Fluvoxamine (FVX) can be reduced at a mercury- drop electrode, with a maximum peak current intensity being obtained at a potential of -0.7 V vs. Ag/ AgCl, in an aqueous electrolyte solution of pH 2. The compound was determined in a pharmaceutical product and in spiked human serum by square-wave adsorptivestripping voltammetry (SWAdSV) after accumulation at the electrode surface, under batch conditions. Because the presence of dissolved oxygen did not interfere significantly with the analysis, it was also possible to determine FVX in the pharmaceutical product by use of a flow-injection analysis (FIA) system with SWAdSV detection. The methods developed were validated and successfully applied to the quantification of FVX in a pharmaceutical product. Recoveries between 76 and 89% were obtained in serum analysis. The FIA– SWAdSV method enabled analysis of up to 120 samples per hour at reduced cost, implying the possibility of competing with the chromatographic methods usually used for this analysis.